An inhibitor of Ca2+-dependent protein kinases, trifluoperazine, increases the efficiency of agrobacterium-mediated transformation of tobacco - Fedorchuk, V.V.; Tanasienko, I.V.; Blume, Y.B.; Yemets, A. I. (Reports of the National Academy of Sciences of Ukraine, 2014)
The influence of different concentrations of the inhibitor of Ca2+-calmodulin-dependent protein kinase, trifluoperazine, on the efficacy of the agrobacterium-mediated transformation of Nicotiana tabacum leaf explants is investigated. It is established that the addition of 10 and 25 μM trifluoperazine into the medium for the co-cultivation with agrobacterium led to increasing the transformation rate up to 98%, that higher by 25% as compared to control. We conducted a series of experiments on the selection of conditions for the agrobacterium-mediated transformation by AGL1 strain that contained plasmid pGH217 and determined the most efficient methodology of genetic transformation.